Ketersampaian masyarakat tani kepada pelaburan saham amanah - Zaimah Ramli, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2010)
In general, people realized that investing in unit trusts is one of the ways to increase savings. However, the question is that do the community as a whole able to access to the unit trusts, especially to those who are in the lower income group. This study tries to measure the rural community that focusing on peasants accessibility to the unit trust. The study also attempts to identify the motivating and the obstacles factors that influence the extend of unit trust accessibility to the group. The study found that, even though the peasant do have general knowledge on the unit trust, their direct involvement and accessibility to it are limited. The primary factor that motivate them to participate in unit trust is the high dividend rate where as the two main factors that hinder their ability to invest are low income and exposure to the unit trust. As a whole, the peasant participation in the unit trust is low and very limited. These phenomena are obvious when most of them are not able to maintain and increase their initial investment value